Nomogram for Estimating the Risks of Intestinal Ischemia and Necrosis in Neonates With Midgut Volvulus: A Retrospective Study - Guan, Xisi; Wang, Zhe; He, Qiuming; Lv, Junjian; Yu, Jiakang; Zhong, Wei (Frontiers in Pediatrics, 2022)
Background: Delayed diagnosis and inaccurate judgment of the severity of the disease may be the principal reasons for the poor prognosis associated with neonatal midgut volvulus. We aimed to develop a nomogram model that timely assesses the risks of intestinal ischemia and necrosis in the neonate with midgut volvulus. Methods: We retrospectively analyzed the clinical data from neonates with midgut volvulus who were admitted to Guangzhou Women and Children’s Medical Center from January 2009 to December 2019. Univariate and multivariate analyses were used to obtain independent factors to build a predictive model. The independent factors were used to develop the nomogram model. Results: Heart rate, mean arterial pressure, serum C-reactive protein, serum sodium, serum albumin, and pH levels were independent predictors for intestinal ischemia and necrosis in patients with midgut volvulus. The area under the receiver operating characteristic curve (AUC) of the predictive model was 0.985 (95% confidence interval, 0.966–0.999; P < 0.001). The sensitivity was 90.48% and the specificity was 93.10%. A nomogram model was established using the six independent predictors, with a C-index of 0.859 and a favorable consistency between the predicted and actual intestinal ischemia and necrosis rates according to the internal validation. Conclusion: The constructed nomogram model could be a superior tool for predicting intestinal ischemia and necrosis in neonates with midgut volvulus.